Perception of products by different levels of integration: A study with pruning shears - Campos, Lívia Flávia de Albuquerque [UNESP]; de Lima Lanutti, Jamille Noretza [UNESP]; de Mattos, Liara Mucio [UNESP]; Pereira, Douglas Daniel [UNESP]; Inokuti, Elen Sayuri [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2012)
Six different models of pruning shears with eight subjects were assessed using semantic differential (SD) applied at four levels of integration: see the product image, see the real product, touch the product, and finally, use the product. The results showed awareness of the variables changed at different levels of interaction. The perception of the subjects changed after using the product.
Keywords: Ergonomic design; Levels of integration; Pruning shears; Semantic differential